Schizophrenia : the final frontier : a festschrift for Robin M. Murray - David, Anthony S.; Kapur, Shitij; McGuffin, Peter; Murray, Robin M., 1944- (Hove, East Sussex : Routledge, 2011)
'Schizophrenia: The Final Frontier is a unique project reflecting the contribution that Robin M. Murray has made to the field of Psychiatry over the past 35 years, with a particular focus on the advances that have been made to the understanding and treatment of schizophrenia. International contributors have been brought together to pay tribute to Robin M. Murray's work and exploring the latest findings in the area. Sections cover: - development in the field - neuroscience - neuroimaging - genetics - cognition - social psychiatry - treatment This book will be essential reading for clinical psychologists, psychiatrists and researchers who work with schizophrenia, as well as admirers of the work of Robin M. Murray'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Schizophrenia; Schizophrenia -- Festschrift